2008
DOI: 10.1148/radiol.2462061469
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Callosum in Patients with Obsessive-Compulsive Disorder: Diffusion-Tensor Imaging Study

Abstract: Study results support the widely held view that the orbital prefrontal region is involved in the pathophysiology of OCD and indicate that the orbitofrontal circuit influences symptom severity in patients with OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 24 publications
2
55
3
Order By: Relevance
“…17,20 However, to our knowledge, no studies to date have investigated the axonal versus myelin contributions to the identified abnormalities in white matter integrity. By examining axial and radial diffusivity in patients with OCD, we have demonstrated that impaired white matter integrity in the body of the CC in this patient group is driven by a myelin abnormality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,20 However, to our knowledge, no studies to date have investigated the axonal versus myelin contributions to the identified abnormalities in white matter integrity. By examining axial and radial diffusivity in patients with OCD, we have demonstrated that impaired white matter integrity in the body of the CC in this patient group is driven by a myelin abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] To date, 8 studies have examined white matter pathology in patients with OCD using DTI. 5,[16][17][18][19][20][21][22] However, the findings of these studies have been variable (Table 1), and no study has examined whether axonal injury or abnormal myelination explains the observed findings. In this study, our aim was to extend previous work and to examine alterations in fractional anisotropy as well as measures of axial and radial diffusivity in a sample of patients with OCD and healthy controls using a well-validated Tract-Based Spatial Statistics (TBSS) technique.…”
Section: Introductionmentioning
confidence: 99%
“…All patients had received a diagnosis of OCD based on the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) [25]. We excluded patients who: had substantial medical illness or neurological (e.g., Tourette syndrome, Huntington disease, and Parkinson disease), pulmonary, cardiac, renal, hepatic, endocrine, or metabolic disorders; had DSM-IV-defined dementia, delirium, schizophrenia, schizoaffective disorder, delusional disorder, brief reactive psychosis, or psychotic disorders not otherwise specified; had DSM-IV-defined mental retardation; had lacunar infarcts; were currently or previously dependent on or abusers of DSM-IVdefined alcoholic or psychoactive substances; and/or were pregnant [26]. For the estimation of obsessive and compulsive symptoms, the Japanese version of the Yale Brown Obsessive Compulsive Scale was applied; its average score was 25.0 ± 8.5.…”
Section: Subjectsmentioning
confidence: 99%
“…Others report that the quality of the WM (the ability to efficiently deliver neuronal signals) may be affected. Several studies (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) report either increased or decreased fractional anisotropy (FA) in OCD. FA is used to evaluate integrity of WM fibre tracts.…”
Section: Introductionmentioning
confidence: 99%